Preparation of Carbon Quantum Dots Based on Willow Leaves as Raw Materials and Their Use as Fluorescent Probes for High-Sensitivity Detection of Pyrophosphatase - Wen, He; Shukai, Wu; Renjie, Cui; Jiaduo, Zhang; Lim, Soh Fong (IOP Publishing Ltd, 2024)
Carbon quantum dots (CQDs) with fluorescent properties were synthesized by onestep hydrothermal method using willow leaves as raw materials, and based on the ability of Cu2+ to form complexes with CQDs and pyrophosphate (PPi), an “off-on-on” fluorescent probe was constructed to realize the selective and highly sensitive detection of pyrophosphatase (PPase). The substance that has been quantified can serve as an indicator for the timely detection of rheumatoid arthritis. The optimal conditions for the preparation of CQDs were investigated, and the optimal reaction temperature was 200℃, the reaction pH was 7.4, and the reaction time was 12h. The FL intensity of different concentrations of pyrophosphatase was measured by using the prepared CQDs as a fluorescent probe and a standard curve was made. It was concluded that PPase had a good linear relationship in the range of 0-0.8 U/mL with the linear equation of Y=- 656.83X+710.43, linear correlation coefficient R2=0.9968, and the recoveries ranged from 98.67% to 102.7%.